Non revenue water at Kuala Lipis - Nor Alina, Alias (2019)
One of the main challenges faced by water utilities is the high NRW level in the water distribution system. In 2015, the NRW rate for Pahang was 52.8% compared with the national average of 35%, the third highest rate among the states in Malaysia. To address this issue, Pahang Water Management Berhad (PAIP) has set up a NRW management unit for its district to monitor NRW rates. For the initial stage, there are only three districts in Pahang State which have special units to control the NRW rate of Kuantan, Kuala Lipis and Pekan. However, this research focuses only on NRW in the district of Kuala Lipis. The NRW unit in Kuala Lipis was established in 2016 after the establishment of DMA. There are nine water treatment plants (WTPs) around Kuala Lipis district equipped with 52 DMAs. The establishment of the DMA commenced in 2014 and completed in 2015. To analyze the effectiveness of NRW management in Kuala Lipis district, the discussion focuses on existing conditions, withdrawals, bills and NRWs for every nine WTPs. Comparison for all WTPs has been made to achieve overall NRW management performance from 2016 to 2018. In addition, NRW components were also identified to know factors that contributed to the rate of NRW. Generally, based on the standard water balance there were three components of NRW that consist of physical losses, commercial losses and unbilled authorised consumption. Based on the analysis made, it shows that the main factor that contributed to water losses is the physical losses as proven by the analysis of water losses for each kilometre pipe of each WTP in this report. It shows that there was 2,027 m3 of water losses occur per day for each kilometer pipe for the year of 2016, 1,800 m3 for the year of 2017 and 1397 m3 for the year of 2018. It is about 5,224 m3 of water loss every day in each kilometre pipe along these three consecutive years. In order to compare flow before and after NRW unit establishment, the analysis made based on the volume of production, billing and NRW for each WTP for three years (2016 until 2018) after the establishment of NRW unit. The comparison of the flow was made based on the baseline rate before the establishment of NRW management. Referring to trend of NRW for all nine WTP, it shows that the rate of NRW varies from year to year and directly proportional to the production and billing rate. There was a lot of difference between the production and billing that occur due to water losses. From all WTP around Kuala Lipis area, only Jelai WTP shown consistence decrease of NRW. This situation occur due to Jelai WTP is the priority since it functions to supply the clean and safe water to the Kuala Lipis city with the highest population rate when compare than others WTP. The highest rate of water losses may lead to insufficient water supply for surround population. Therefore, the overall monitoring and management started at the Jelai WTP which provide supply to the town. For other WTP, the overall monitoring and management would be carried out according to priority due to lack of manpower.